A dansyl-based fluorescent probe for the highly selective detection of cysteine based on a d-PeT switching mechanism. Issue 34 (12th April 2017) - Xiao, Yudong; Guo, Yujin; Dang, Ruili; Yan, Xin; Xu, Pengfei; Jiang, Pei
Abstract : A novel fluorescent probe DN-C for detection of cysteine (Cys) based on d-PeT switching mechanism was reported. Abstract : A novel fluorescent probe, DN-C, for detection of cysteine (Cys) based on a d-PeT switching mechanism is reported. In the presence of Cys, the probe exhibits a turn-on fluorescence signal and nearly 28-fold fluorescence intensity enhancement. The cellular imaging experiment indicated theDN-C possess desirable cell permeability for biological applications.